The relationship between landscape planting patterns and perceived safety in urban parks in Tabriz, Iran - Hami, Ahmad; Maulan, Suhardi; Mariapan, Manohar; Malekizadeh, Muhammad (Academic Journals, 2014)
The relationship between plants and perceived safety in residential areas has been argued by landscape researchers, but there is inadequate or no relevant literature available on the effect of plants in urban parks’ safety. Therefore, a photo-questionnaire survey was conducted among urban park users in Tabriz, Iran to gauge the perceived safety of landscape scene with diverse types of texture to discover its effectiveness, especially in relation to the content of the scene. The survey was composed of 296 participants in November, 2012. The result suggested that landscape scene with vast aspect and physical access was perceived safer than the scene with crowded plants and blocked view. The findings demonstrated that a scene without lawn and water is perceived to be less safe than a scene with lawn and features of water. Moreover, landscape scene with more plant species was unsafe as compared to a scene with fewer plant species. This study proved that a landscape designed with ground cover such as lawn, grass and water feature implies increment of perceived safety in urban parks. Likewise, landscape designers should avoid crowded planting in areas, which obstructs visibility in urban parks and reduces perceived safety. The results expand the application of routine activity (RA) theory in park landscape design in Tabriz, Iran.